Spatialisation de l’apparaître : le volume et le rythme - Éliane Escoubas (Projets de Paysage)
The investigation of spatialization finds its starting point in the notion of “phenomenon” – which is the “appearing” of what appears. The appearing does not appear among the appearing things, it is their appearance – being itself invisible. Everyday, we content ourselves with “seeing” things – seeing what is (only art, under its various forms, brings the “appearing” of what is, to the appearance). The appearing turns out to be the “volume”, by its co-genesis with the human body, and in the “rhythm” as a field of tensions in permanent movement. Thus, two philosophers –phenomenologists are summoned: Max Loreau and Henri Maldiney.